2014
DOI: 10.1002/embr.201338126
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic functions of LMNA isoforms in energy expenditure and lifespan

Abstract: Alternative RNA processing of LMNA pre-mRNA produces three main protein isoforms, that is, lamin A, progerin, and lamin C. De novo mutations that favor the expression of progerin over lamin A lead to Hutchinson-Gilford progeria syndrome (HGPS), providing support for the involvement of LMNA processing in pathological aging. Lamin C expression is mutually exclusive with the splicing of lamin A and progerin isoforms and occurs by alternative polyadenylation. Here, we investigate the function of lamin C in aging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 26 publications
(40 reference statements)
6
60
0
Order By: Relevance
“…4b). Noteworthy, recently, it has been shown that LMNA isoforms lamin C and progerin have distinct and opposite functions regarding energy expenditure and lifespan (Lopez-Mejia et al 2014). There are other examples of other protein isoforms that differ in several biological aspects despite being generated from the same gene (reviewed in Stamm et al 2005).…”
Section: Resultsmentioning
confidence: 98%
“…4b). Noteworthy, recently, it has been shown that LMNA isoforms lamin C and progerin have distinct and opposite functions regarding energy expenditure and lifespan (Lopez-Mejia et al 2014). There are other examples of other protein isoforms that differ in several biological aspects despite being generated from the same gene (reviewed in Stamm et al 2005).…”
Section: Resultsmentioning
confidence: 98%
“…A deficiency of both lamin A and lamin C causes death in mice from muscular dystrophy/cardiomyopathy (12), but the elimination of lamin C synthesis alone or lamin A synthesis alone has no obvious adverse effects (13)(14)(15). For example, "lamin C-only" knockin mice, in which all of the output of the Lmna gene is channeled into the production of lamin C, are free of disease phenotypes and have a normal life span (13).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the genes selected, such as PLIN2, SORT1, PLIN1, MTTP, ACACA, ACLY, ENO3, FASN, ACVR1C, PLTP and CES3 are well known for their role in energy and lipid metabolism (Supplementary Table S1), while LMNA, INSIG2 and NAMPT are not directly involved in lipid metabolism but have already been considered in other species for a putative role in adipogenesis or lipid metabolism. LMNA, whose main role is related to nuclear stability and chromatin structure, also has a putative role in fat deposition (Verstraeten et al, 2011;Lopez-Mejia et al, 2014) and for this reason was included among the genes selected. Furthermore, INSIG2 was reported by Malzahn et al (2014) as a gene associated with the body mass index in humans, even if this association is still under debate.…”
Section: Introductionmentioning
confidence: 99%